2013
DOI: 10.1093/aepp/ppt004
|View full text |Cite
|
Sign up to set email alerts
|

Do Environmental Interventions Impact Elementary School Students' Lunchtime Milk Selection?

Abstract: This research examines whether environmentally based intervention strategies increase elementary students' selection of white milk. At intervention school one, white milk was easily accessible, but students had to ask for chocolate milk. As an outcome, students increased their selection of white milk compared to control school students (p≤0.001). At intervention school two, the visual cue of a threefold greater quantity of white compared to chocolate milk did not significantly alter selection patterns. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…Following the assumptions on order and isolation effects, a different possibility for increasing the choice of specific food options has been the manipulation of defaults in a menu. For school children, the creation of white milk as a default option—in contrast to the ineffective ban of chocolate milk discussed in Subsection 3.1.1—was effective in increasing its choice compared to chocolate milk significantly without increasing leftovers (Goto, Waite, Wolff, Chan, & Giovanni, ). The effectiveness of a default for influencing food consumption nevertheless seems to decrease when options become too different with respect to their attractiveness since Wansink and Just () found that apple slices as default option for a kids fast‐food menu were mainly levered out from children's strong preferences for the other option, French fries and the resulting active choice against the default.…”
Section: Resultsmentioning
confidence: 99%
“…Following the assumptions on order and isolation effects, a different possibility for increasing the choice of specific food options has been the manipulation of defaults in a menu. For school children, the creation of white milk as a default option—in contrast to the ineffective ban of chocolate milk discussed in Subsection 3.1.1—was effective in increasing its choice compared to chocolate milk significantly without increasing leftovers (Goto, Waite, Wolff, Chan, & Giovanni, ). The effectiveness of a default for influencing food consumption nevertheless seems to decrease when options become too different with respect to their attractiveness since Wansink and Just () found that apple slices as default option for a kids fast‐food menu were mainly levered out from children's strong preferences for the other option, French fries and the resulting active choice against the default.…”
Section: Resultsmentioning
confidence: 99%
“…About half of the 55 studies were randomized controlled trials 46,4955,5763,6571,7375,7780, 8385, 9698, 109110, 112118, 121124, 127129, 133 (29; 53%). The remaining studies utilized quasi-experimental designs, with either a two-group 64,76,86–90,104,106,111,119120,125,130132 (11; 20%), or one-group pretest-posttest 4748,56,72,8182,9195,99103,105,107108,126 (15; 27%) design.…”
Section: Resultsmentioning
confidence: 99%
“…Additional settings included home 6667,109,112113 (4; 7%), clinic 4748,56,65,6869,7375,7779 (7; 13%), and community-based organizations 8185,103 (5; 9%). Twenty of 55 (36%) studies identified SSB as their sole focus 56, 6264, 7072, 8485, 90, 96, 9899, 105106, 109, 112113, 120–125, 133 . Of the 55 studies, a third (19; 35%) were conducted internationally 46, 4954, 5760, 6264, 7780, 100, 106, 109110, 115124, 127129, 133 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, many school districts have begun to limit or ban the sale of chocolate milk in hopes of reducing students' total caloric and sugar intake. [1] In contrast, the predominant view of nutrition and medical researchers is that milk has nutrients essential for bone growth and development, [2,3,4,5,6] leading other school districts to take the position that any milk is better than no milk. [7,8,9] What is not known, however, is whether or not changing the availability of chocolate milk would influence other behaviors such as within-meal compensation [10] or after-school snacking patterns.…”
Section: Introductionmentioning
confidence: 99%